Melasma in the United States: A cross-sectional study of prevalence data using the All of Us database - Kritin K Verma; Venkata S Dasuri; Daniel P Friedmann (Journal of Dermatology and Dermatologic Surgery, 2023)
Background: Although melasma is a common acquired facial dyschromia, its epidemiology in the general population has not been clearly elucidated. Purpose: To investigate the prevalence of melasma and its correlation with demographic factors, such as age and race, using the All of Us open-access database initiative from the National Institutes of Health in the United States. Methods: A cross-sectional statistical analysis of patients with a diagnosis of melasma in the All of Us open-access database initiative from the National Institutes of Health was performed. Results: A total of 744 reported cases of melasma were found in a population of 407,333 patients (0.18% prevalence) with a 19:1 female-to-male ratio. Patients in the 41–55 age groups had the highest prevalence and Hispanic and Asian patients were three times more likely to be represented than white and black patient populations. Conclusion: Asian and Hispanic race and a 41–55 year age group are correlated with a significantly greater prevalence of melasma. The prevalence rate for melasma in this database may be far lower than prior reported rates due to incorrect or missed coding within this database, which is billing code dependent.